The importance of periodontal screening in children. A case report. (2nd June 2021) - Capaldi, Francesca; Besi, Eleni; Roebuck, Elizabeth M
Abstract : The British Society of Periodontology, in collaboration with the British Society of Paediatric Dentistry, published guidelines in 2012 for the periodontal screening of children and adolescents. The guidelines recommended a simplified Basic Periodontal Examination (BPE) of six teeth for children aged 7–17 years. This is further modified for ages 7–11, using codes 0–2 from the 0–4 BPE adult chart. An unusual case of an 11-year-old boy who attended his general dental practitioner for a check-up is reported. Periodontal screening led to the detection of 13-mm pockets associated with the two mandibular first permanent molars that required surgical intervention and multidisciplinary care. CPD/Clinical Relevance: This case report highlights the importance of paediatric periodontal screening in both primary and secondary care.